A replication study of language development in the writing of Malaysian Chinese learners of English / Ng Lee Kean - Ng , Lee Kean (2017)
The present study is an approximate replication of Larsen-Freeman’s (2006) research entitled “The Emergence of Complexity, Fluency, and Accuracy in the Oral and Written Production of Five Chinese Learners of English”. Larsen-Freeman investigated the language development that takes place in learners’ writing over time based on Complex Dynamic Theory. Learner language development is found to be neither consistent nor stage-like. It fluctuates. Language resources of learner change through use and thus, give rise to a novel version. The study replicates the procedure of data collection and qualitative data analysis of Larsen-Freeman’s study, but changes the data production. The writing of five Malaysian Chinese L2 learners based on a picture series were analysed using the idea unit analysis of the original study. In addition, the narratives of the participants were assessed by three raters using the current holistic scoring in Form Three Assessment Examination or PT3. The purpose of this research is to find out whether the changes observed from the learners’ writing over time based on the idea unit analysis concur with the original research. It is also aimed to see the differences between the results of the idea unit analysis and the results of holistic scoring. The replication study showed that the results of Larsen-Freeman’s (2006) study apply to these five participants. However, a comparison of the results from the idea unit analysis with the scores from holistic scoring showed that there are some disparities between the two methods of assessing. The idea unit analysis helps teachers observe language development of the learners in details and may be used as an alternative to holistic scorings.